Penanggulangan Kemiskinan: Kebijakan dalam Perspektif Gerakan Sosial - J. Nasikun (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
The poors have been ignored within the process of economic development, as myth of non-existence reveals. More over, they have been discredited as the attempt to recognise their existence become a liability. It is widely assumed that policies in favour to the poor essentially compromising the interest of the growing economy. Based on this kind of